PENCEGAHAN PENULARAN PENYAKIT INFEKSI DAN PEMANTAUAN PERTUMBUHAN BALITA UNTUK MENGATASI STUNTING DI TEMPAT PENITIPAN ANAK - Mitra, Mitra; Rany, Novita; Herniwanti, Herniwanti; Syifa, Ervira Dwiaprini As (LPPM Universitas Flores, 2024)
Daycare centres (TPA) play an essential role in supporting mothers in caring for their children, especially for working mothers. Daycare centres are one of the alternatives for mothers to replace their role in caring for their children while they are at work. However, TPA is often a place where the transmission of infectious diseases such as diarrhoea, respiratory infections, and other diseases occurs quickly due to close interaction between children. Therefore, preventing the transmission of infectious diseases in TPA is an important step to prevent stunting. In addition, monitoring of children's growth has yet to be done routinely in the TPA. The purpose of this community service is to increase knowledge for mothers and landfill managers in preventing transmission of infectious diseases and monitoring the growth of toddlers, as well as practical steps in maintaining the personal hygiene of children and the environment and the availability of educational media in the form of posters, leaflets and videos. The targets of the service are mothers of toddlers and landfill managers. The service method provides education, distributes hygiene tools, and provides educational media, namely posters, leaflets, and videos. The evaluation was carried out by distributing questionnaires before and after counselling. The service results showed increased knowledge of mothers of toddlers and landfill managers. The results of growth monitoring show that participating toddlers have good nutritional status and can practice hand washing properly. Although there are obstacles, such as the limited number of participants, this activity positively impacts increasing awareness about stunting prevention. The subsequent development is to expand the reach of education by involving more TPAs and introducing digital monitoring methods through applications to monitor children's growth. Support from relevant agencies is needed to ensure the sustainability of the programme.